2017
DOI: 10.1097/mpg.0000000000001498
|View full text |Cite
|
Sign up to set email alerts
|

Diverting Ileostomy for the Treatment of Severe, Refractory, Pediatric Inflammatory Bowel Disease

Abstract: In pediatric patients with refractory colonic IBD, diverting ileostomy can be a successful intervention to induce clinical stability. Importantly, diversion is a steroid-sparing therapy and allows additional time to clarify the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…8,11 In addition, the extent and location of disease can change and progress over time, and patients who present with exclusive colonic disease can later develop perianal and small bowel disease. 12 Therefore, indeterminate colitis is diagnosed more often in patients with VEO-IBD (11%-22%) as compared to older onset IBD (4%-10%). 9,[13][14][15] Because of this colonic involvement, patients with VEO-IBD are also more commonly diagnosed with UC (35%-59%) as compared to older onset IBD (older children > 6 and adults) in which CD is more prevalent (55%-60%).…”
Section: Disease Classificationmentioning
confidence: 99%
“…8,11 In addition, the extent and location of disease can change and progress over time, and patients who present with exclusive colonic disease can later develop perianal and small bowel disease. 12 Therefore, indeterminate colitis is diagnosed more often in patients with VEO-IBD (11%-22%) as compared to older onset IBD (4%-10%). 9,[13][14][15] Because of this colonic involvement, patients with VEO-IBD are also more commonly diagnosed with UC (35%-59%) as compared to older onset IBD (older children > 6 and adults) in which CD is more prevalent (55%-60%).…”
Section: Disease Classificationmentioning
confidence: 99%
“…Fahy et al reported that in paediatric patients with severe refractory Crohn's colitis, total colectomy offers an opportunity to improve nutrition and growth and reduce steroid use with a reasonable likelihood of restoring intestinal continuity [18]. Maxwell et al reported that in paediatric patients with refractory colonic IBD, a diverting ileostomy can be a successful intervention to induce clinical stability [19]. In our study, the surgical approach allowed patients to decrease the use of metronidazole, thalidomide and other drugs.…”
Section: Discussionmentioning
confidence: 61%
“…Some studies have reported higher surgical rates in children with VEO-IBD, especially those with infantile IBD [56,57]. However, the Canadian cohort of patients with VEO-IBD showed a low frequency of surgical interventions in the younger group than in the older pediatric group [2].…”
Section: Surgerymentioning
confidence: 95%